2018
DOI: 10.1002/em.22184
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling in healthy newborns from diverse localities of the Czech Republic

Abstract: Prenatal exposure to air pollution is associated with intrauterine growth restriction and low birth weight. Gene expression changes in newborns in relation to air pollution have not been sufficiently studied. We analyzed whole genome expression in cord blood leukocytes of 202 newborns from diverse localities of the Czech Republic, differing among other factors in levels of air pollution: the district of Karvina (characterized by higher concentration of air pollutants) and Ceske Budejovice (lower air pollution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…In our investigation, we could not directly examine whether non-atopic asthma represents T-helper 2 or type 2 low asthma, while atopic asthma captures Thelper 2 or type 2 high asthma, two known endotypes [3,30]. This is because we did not measure typical [9,10,13,19,[31][32][33][34][35][36]. Both the laboratory and epidemiologic evidence have shown that PAHs could induce or enhance allergic sensitization, exacerbate pre-existing asthma, and enhance the risk of de novo asthma development [33,37,38].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our investigation, we could not directly examine whether non-atopic asthma represents T-helper 2 or type 2 low asthma, while atopic asthma captures Thelper 2 or type 2 high asthma, two known endotypes [3,30]. This is because we did not measure typical [9,10,13,19,[31][32][33][34][35][36]. Both the laboratory and epidemiologic evidence have shown that PAHs could induce or enhance allergic sensitization, exacerbate pre-existing asthma, and enhance the risk of de novo asthma development [33,37,38].…”
Section: Discussionmentioning
confidence: 96%
“…cigarette smoke and other anthropogenic compounds) have been shown to predict de novo asthma development during childhood [8]. Our group too has documented signi cant associations among neighborhood level of polyaromatic hydrocarbon (PAH), speci cally, benzo[a]pyrene (B[a]P), multiple putative biomarkers, and clinically diagnosed asthma in children [9][10][11][12][13][14][15]. Furthermore, our analysis suggest for the rst time that childhood B[a]P exposure predicts dose-responsive, integrative -Omics based mechanisms of asthma, mediated by dysregulated hematopoiesis among the asthma cases, compared to the controls [11].…”
Section: Introductionmentioning
confidence: 99%
“…It significantly increased in newborns in Karvina. DNA adducts [ 52 ], oxidative damage (DNA oxidation, lipid peroxidation) [ 53 ], and whole genome expression revealed a deregulation of processes associated with immune response or oxidative stress response [ 54 ]. In the urine of newborns, monohydroxylated metabolites of PAHs (OH-PAHs) were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Honkova et al [40] analyzed whole genome expression in cord blood of leukocytes of 202 newborns from the districts of Karvina and Ceske Budejovice. They aimed to identify differentially expressed genes and pathways in relation to locality and concentration of air pollutants.…”
Section: Impact Of Air Pollution On the Genome Of Newbornsmentioning
confidence: 99%